Professor, você faz as unhas?: das experiências escolares às políticas curriculares no ensino de história - Silva, Guilherme Henrique da (2022)
The present research intended to comprehend the Other’s place in the formation made possible by the History curriculum adopted by the state of São Paulo during the COVID-19 pandemic. For that purpose, we have proposed to identify the curriculum’s policy created for the specific pandemic scenario; to highlight the sensitive experiences that took place in the classroom regarding the place of the Other and of the Difference; and to analyze the narratives the students produce about the place of the Other and the Difference, reflecting on the possibilities of teaching History in the context of socially alive issues. By proposing this investigation, we consider that the coexistence of different curriculum conceptions allows scholastic trajectories and their effects to be seen from different perspectives. Each curriculum presupposes a certain conception of the subject who, at times, emancipates, at times reproduces dominations or reduces subjects in their experiences. In the current pandemic scenario, this research was built from the beginning of my teaching career, in just over three months in remote teaching. The concern about the emancipation of subjects in the curriculum proposed by the State of São Paulo happened from the observation that the teaching of canonical contents were greatly present in the History curriculum and, in a certain way, unquestionable by the school's culture. This perception, from my position as a history teacher, raised the central question for this dissertation: What is the place of the Other and the Difference in the discipline of history in São Paulo's curriculum during the pandemic? Seeking possible answers, we have anchored the discussion in the the theoretical and methodological assumptions of hermeneutic phenomenology, intending to emphasize the meanings students from the final years of Elementary School attribute to the contents studied in History classes produced by the Centro de Mídias do Estado de São Paulo (CMSP) during the months of april through july 2021. The instruments used in data collection were the application of a questionnaire, notes in a personal observation journal, documents and a bibliographic study. The analysis was based on the theory of interpretation. The carried out studies allowed us to understand how the proposed curriculum contributes to the non acceptance of issues sensitive to the emancipation of subjects who submit to its proposals, which demonstrates the permanence of a traditional perspective of History Curriculum and its teaching. In turn, a proposal of a Teaching of History that allows for alterity remains invisible in the school space. Finally, we note how the proposal of emancipatory curriculum policies that subvert the linearity still imposed in such practices is still absent. It was evidenced that the Other and the Difference are not included in the official curriculum. However, in the daily life of the school, in the students' speeches, and in the teacher's practice, this Other and the Difference appear; they are there in the classroom, when they are not themselves – teachers and students – the Other and the Difference.